Utilization of gonad sea urchin for cookies product as a potential local resources in preventing stuting in Linsowu Village North Buton Regency - Rosdarni, Rosdarni; Muslimin, La Ode; Kartini, Sapril; Muslimin, Yuliana; Siharis, Fatma Sari; Kusumawati, Ita Rahmania (Research and Social Study Institute, 2024)
Stunting is a child's growth and development disorder caused by a lack of nutritional intake, infection, or inadequate stimulation. The impact of stunting includes decreased intelligence, vulnerability to disease, hampered economic growth and work productivity, and exacerbated inequality. The aim of this service is to provide information, knowledge, and education about the processing of sea urchins into cookies as a local resource with the potential to prevent stunting. This community service aims to educate through outreach and counseling using a food diversification approach for participants. The service was carried out in one of the houses of Linsowu Village residents, involving 47 participants in the socialization session and 27 participants in the counseling session. The target children, who were given cookies, included 11 children suffering from stunting. The PKM activities were conducted over 2 days, starting with the socialization stage on the first day and counseling on the following day, which focused on live demonstration activities related to the procedures for making sea urchin gonad-based cookies. The result of this activity is a cookie product made from sea urchin gonads, ready to be consumed by children suffering from stunting, made from Soroaki and Taeo gonads. Based on taste and preferences, cookies with a mixture of pineapple jam and Soroaki gonads were the most popular with both participants and stunted children.